Generation and characterization of ABBV642, a dual variable domain immunoglobulin molecule (DVD-Ig) that potently neutralizes VEGF and PDGF-BB and is designed for the treatment of exudative age-related macular degeneration. Issue 2 (17th February 2017) - Ding, Kun; Eaton, Lucia; Bowley, Diana; Rieser, Matthew; Chang, Qing; Harris, Maria C.; Clabbers, Anca; Dong, Feng; Shen, Jikui; Hackett, Sean F.; Touw, Debra S.; Bixby, Jacqueline; et al.
ABSTRACT: Exudative age-related macular degeneration (AMD) is the most common cause of moderate and severe vision loss in developed countries. Intraocular injections of vascular endothelial growth factor (VEGF or VEGF-A)-neutralizing proteins provide substantial benefit, but frequent, long-term injections are needed. In addition, many patients experience initial visual gains that are ultimately lost due to subretinal fibrosis. Preclinical studies and early phase clinical trials suggest that combined suppression of VEGF and platelet-derived growth factor-BB (PDGF-BB) provides better outcomes than suppression of VEGF alone, due to more frequent regression of neovascularization (NV) and suppression of subretinal fibrosis. We generated a dual variable domain immunoglobulin molecule, ABBV642 that specifically and potently binds and neutralizes VEGF and PDGF-BB. ABBV642 has been optimized for treatment of exudative AMD based on the following design characteristics: 1) high affinity binding to all VEGF-A isoforms and both soluble and extracellular matrix (ECM)-associated PDGF-BB; 2) potential for extended residence time in the vitreous cavity to decrease the frequency of intraocular injections; 3) rapid clearance from systemic circulation compared with molecules with wild type Fc region for normal FcRn binding, which may reduce the risk of systemic complications; and 4) low risk of potential effector function. The bispecificity of ABBV642 allows for a single injection of a single therapeutic agent, and thus a more streamlined development and regulatory path compared with combination products. In a mouse model of exudative AMD, ABBV642 was observed to be more effective than aflibercept. ABBV642 has potential to improve efficacy with reduced injection frequency in patients with exudative AMD, thereby reducing the enormous disease burden for patients and society.